Investigations into novel small molecules as potential treatments for idiopathic pulmonary fibrosis and malaria - Park, Jozef (2022)
Small molecules provide relatively inexpensive therapeutics for a range of conditions. In contrast with antibody-conjugate treatments and more elaborate treatment options, use of small molecules makes treatment affordable and accessible for all, around the world. This thesis details research into the development of novel small molecule inhibitors of the αV β6 integrin as potential therapeutics for conditions such as idiopathic pulmonary fibrosis (IPF), and also small molecules as therapeutic agents against Plasmodium falciparum for the treatment of malaria.